Perancangan Sistem Informasi Penjualan dan Pengendalian Stock Barang dengan Metode EOQ dan Reorder Point - Ridho Musta; E Erdisna (Jurnal Informasi dan Teknologi, 2020)
This research aims to control the stock of goods more effectively and efficiently. Stock data is controlled from sales transactions that occur at any time with online. This study processes sales data at the Epi Rice Shop. The method used in controlling stocks is Economic Order Quantity (EOQ) and Reorder Point. The data is processed by PHP programming language and MySQ Database. Processing results are presented in the form of reports relating to sales and inventory information. Reports produced can control the stock of goods better because of clearer and more accurate information, so the error rate in controlling stock is relatively small. So that this research can be used in ordering and controlling stock of goods to be more effective and efficient.